2007
DOI: 10.1007/s00535-007-2061-9
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of single and repetitive percutaneous transhepatic gallbladder aspiration for the treatment of acute cholecystitis

Abstract: For the treatment of acute cholecystitis that does not react to conservative therapies, PTGBA is a safe, simple, and effective treatment modality that can be performed at bedside without any severe complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Repetitive PGBA (2-4 times) was reported in four studies, including two that used antibiotic instillation, and had clinical success rates of 76% to 96% and complication rates of 0% to 3%. Th e two studies with antibiotic instillation had clinical success rates of 95% and 96% ( 7,8 ), and the other two studies without antibiotic instillation had clinical success rates of 76% and 92% ( 9, 10 ). Repetitive PGBAs had success rates of 47% to 96% in patients who did not improve with a single PGBA (7)(8)(9)(10).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Repetitive PGBA (2-4 times) was reported in four studies, including two that used antibiotic instillation, and had clinical success rates of 76% to 96% and complication rates of 0% to 3%. Th e two studies with antibiotic instillation had clinical success rates of 95% and 96% ( 7,8 ), and the other two studies without antibiotic instillation had clinical success rates of 76% and 92% ( 9, 10 ). Repetitive PGBAs had success rates of 47% to 96% in patients who did not improve with a single PGBA (7)(8)(9)(10).…”
Section: Resultsmentioning
confidence: 97%
“…Th e complication rate was 0% ( 3,6,9 ). One randomized controlled study and six observational studies reported that 0% to 43% of patients required salvage PC and 0% to 7% of patients required surgery, either due to lack of improvement of symptoms, patient preference, or procedure-related complications ( 3,4,(6)(7)(8)(9)(10). Two observational studies reported immediate pain control rates of 99% to 100% ( 9, 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(24,25,26) However, recently the usefulness of PTGBA has been reported. (27,28,29) Previously in our hospital PTGBD were performed in principle for AC. In fact the effect of drainage of PTGBD is superior to that of PTGBA.…”
Section: Discussion Discussionmentioning
confidence: 99%